Anti-Müllerian Hormone (AMH) Profiles as a Novel Biomarker to Evaluate the Existence of a Functional Cryptorchid Testis in Japanese Black Calves - KITAHARA, Go; SHIRAO, Yuka; KAMIMURA, Shunichi; SATO, Tomohiro; ALI, Hossam EL-SHEIKH; KOBAYASHI, Ikuo; HEMMI, Koichiro (Journal of Reproduction and Development, 2012)
Anti-Müllerian hormone (AMH) and testosterone (T) profiles in blood were investigated before and after an hCG stimulation test to assess their sensitivity and specificity for the existence of a functional cryptorchid testis in Japanese Black calves. The hCG (3,000 IU) was administered on Day 0, and peripheral blood was collected on Days 0 (just before hCG injection), 5 and 7 in intact male calves (Intact; n=19), bilateral castrated calves (Castrated; n=17), unilateral cryptorchid calves, which abdominal testis could been extracted (Uni-crypto; n=9). Castration of a descended testis was carried in the Castrated and Uni-Crypto groups on Day -14. The AMH detectability and the optimum cut-off point for T levels using the receiver operating characteristic curve were verified to characterize the cryptorchid testis. AMH values on Day 0 were 21.1 ± 5.1 and 29.0 ± 7.5 ng/ml in the Intact and Uni-crypto groups, respectively (Mean ± SEM). AMH levels were under the detection limit in the Castrated group (i.e., < 0.006 ng/ml). T showed its peak levels on Day 5 in the Intact group (26.8 ± 4.2 ng/ml), while it remained low in the Castrated group (< 0.9 ng/ml) and did not show a significant difference in the Uni-crypto group. The detectable levels for AMH was 0.006 ng/ml, and the optimum cut-off point for T was 0.9 ng/ml; the sensitivity and specificity for evaluation of testicular descent into the scrotum were 1.0 for both the AMH and T levels. The detection rates in the Uni-crypto group using them were 1.0 and 0.57 for AMH on Day 0 and T on Days 5 or 7, respectively. In conclusion, plasma AMH profiles could be used as a novel biomarker to evaluate the existence of a functional cryptorchid testis in Japanese Black calves.